2018
DOI: 10.1016/j.ijid.2018.04.3972
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pictogram intervention in identification and reporting adverse drug reactions in Naïve HIV patients in Ethiopia

Abstract: Background: Adverse drug reactions (ADRs) to antiretroviral medications remained important reasons of concern that may compromise the effectiveness of the ART programs. In health communication, pictograms has a comprehensive place to aid attention, memory recall and promote adherence. In this study, we sought to assess whether this intervention would help to identify and improve ADR reporting in an ART clinic serving HIV patients in Northwest Ethiopia. Methods & Materials: A cross-sectional study on ART-naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A further study by the same group was undertaken in Tanzania [ 35 ] using similar materials for ART in Kiswahili, with pictograms, and again reported the acceptability and comprehensibility of this form of written information. An Ethiopian RCT found that pictograms aided the identification of medicines, but not identification of ADRs [ 34 ]. Pictograms were preferred by 41% of patients in a study in Cameroon, but symbols were most easily understood, by 90% [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A further study by the same group was undertaken in Tanzania [ 35 ] using similar materials for ART in Kiswahili, with pictograms, and again reported the acceptability and comprehensibility of this form of written information. An Ethiopian RCT found that pictograms aided the identification of medicines, but not identification of ADRs [ 34 ]. Pictograms were preferred by 41% of patients in a study in Cameroon, but symbols were most easily understood, by 90% [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only very few papers reported a small impact of education training. One of these was the training of naïve HIV-positive patients with limited literacy to identify and report ADRs using pictorial representation (23).…”
Section: Educational Interventionsmentioning
confidence: 99%